Epilogue: [Epilog] - Surijah, Edwin Adrianta (Faculty of Psychology, Universitas Surabaya, 2023)
Epilogue from Edwin Adrianta Surijah regarding their time as an Editor-in-Chief in ANIMA Indonesian Psychological Journal. Epilog oleh Edwin Adrianta Surijah perihal waktu mereka menjabat sebagai Editor-in-Chief di ANIMA Indonesian Psychological Journal.